(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2026)
This study aims to develop Canva-based learning media that are valid, practical, and effective in improving students’ conceptual understanding of the System of Linear Equations in Two Variables (SLETV) among eighth-grade students at SMP Negeri 1 Padang Bolak Julu. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research instruments consisted of questionnaires and tests to measure the validity, practicality, and effectiveness of the media. The validation results indicated that the Canva-based learning media met the valid criteria, with an average score of 75% from media experts, and were categorized as highly valid in the material and language aspects with scores above 80% and 91.4%, respectively. The practicality tests conducted by teachers and students obtained scores of 96% and 90.02%, respectively, categorized as very practical, while the effectiveness test showed a high N-Gain value, indicating a significant improvement in students’ conceptual understanding. The novelty of this study lies in the integration of the Canva platform as a systematically designed interactive digital medium that supports engaging, communicative, and meaningful mathematics learning. The results indicate that the Canva-based learning media improved students’ conceptual understanding of the system of linear equations in two variables. In addition, the learning process showed increased student participation compared to the pre-implementation stage.